The relationship between literacy rate and crime rate: An analysis with reference to Kerala - Jaison V Joseph and Jomon Mathew
The crime rate in India has been on rise. It becomes important to study the factors that impact the crime rate. It is expected that more the literacy rate of a state, the less the crime would be. Though crime has more to do with psychological factors, a negative relationship can be expected in literacy rate and crime rate. The present paper attempted to evaluate this correlation in case of Kerala. The analysis shows that crime statistics is one important reason to rethink the famed Kerala model of development. The general understanding that literacy rate and crime rate are negatively correlated has not proved correct in case of Kerala. In this context, the government and administrators should take steps to control the special type of crimes in Kerala as ag ainst that of other states. Police authorities and others should actively interfere in each case and identify the problems of each case rather than a peripheral case analysis. The service of psychologists in each police station is essential. The availability of intoxicants in the state has to be reduced. The state has higher potential to improve the law maintenance if the educated generations are properly guided